Promoting Mental Wellbeing Among The Saudi Healthcare Workers: Lessons From The Global Wellness Programs (Journal of Namibian Studies : History Politics Culture, 2022)
Sound mental health among the health workers is a desire of every healthcare institution. While it can be difficult to evade occasional instances of mental health problems among healthcare workers, the healthcare management need subtle programs for addressing any spotted case of mental health problem among the professionals. The mental care programs would be beneficial to Saudi Arabia where prevalence of depression, stress and anxiety are on high level. Unfortunately, most of the established mental wellness programs, such as mindfulness initiatives have only been densely applied in the high-income countries. This narrative review explored how these programs can be applied to the Saudi healthcare context. Accordingly, three considerations should be made; sensitivity to working hours and religious practices, leveraging family and community support systems, and addressing stigma surrounding mental health.